EFEKTIVITAS PELAKSANAAN PERAN KELOMPOK SIAGA BENCANA KELURAHAN OLO DALAM UPAYA MITIGASI BENCANA GEMPA BUMI DAN TSUNAMI DI KAWASAN PANTAI PADANG - Chece Syahyanti; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
The State of Indonesia is one of the countries prone to disasters, including the City of Padang. Thousands or even hundreds of thousands of people have become victims of natural disasters in Indonesia, including the earthquake and tsunami. Based on data from the Padang City Statistics Agency that the District in the City of Padang consists of 11 districts with a total of 104 villages. However, data from the Padang City Disaster Management Plan (RPB) the level of disasters in the kelurahan varies such as areas located in coastal areas, automatically the level of disaster risk that occurs is also high, one of which is Olo Kelurahan, then to undertake earthquake disaster mitigation efforts earth and tsunami formed the Disaster Preparedness Group. This study aims to determine the effectiveness of the implementation of the role of the Olo Village Disaster Preparedness Group in efforts to mitigate earthquakes and tsunamis in the Padang Beach region. This type of research is descriptive using qualitative methods. The results showed that the implementation of the role of the Olo Village Disaster Preparedness Group in efforts to mitigate the earthquake and tsunami in the Padang Beach area could be said to be ineffective. The problems encountered include: lack of education and training received, lack of funds / budget, inadequate facilities and infrastructure, lack of meetings conducted, lack of member activity, and lack of socialization given. This type of research is descriptive using qualitative methods. The results showed that the implementation of the role of the Olo Village Disaster Preparedness Group in efforts to mitigate the earthquake and tsunami in the Padang Beach area could be said to be ineffective. The problems encountered include: lack of education and training received, lack of funds / budget, inadequate facilities and infrastructure, lack of meetings conducted, lack of member activity, and lack of socialization given. This type of research is descriptive using qualitative methods. The results showed that the implementation of the role of the Olo Village Disaster Preparedness Group in efforts to mitigate the earthquake and tsunami in the Padang Beach area could be said to be ineffective. The problems encountered include: lack of education and training received, lack of funds / budget, inadequate facilities and infrastructure, lack of meetings conducted, lack of member activity, and lack of socialization given.